PENILAIAN MUTU ORGANOLEPTIK IKAN MUJAIR (Tilapia mossambica) SEGAR DENGAN UKURAN YANG BERBEDA SELAMA PENYIMPANAN DINGIN - Taher, Nurmeilita (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
ï»¿Tilapia fish production is available almost all year round, so fish is easy to obtain and economic value. Use of low temperature 0Â°C on wet fish can prolong the process rigormortis, can suppress bacterial activity, chemical and organoleptic changes. This study aims to determine the effect of different weights to the organoleptic quality of tilapia fish during cold storage. Observations made include a description of the eyes, gills, and texture and odor panel using a team of 15 people. The results showed that weight did not influence the quality of tilapia fish orgnoleptic. And storage of up to 2 days, fish is still fresh classified.